Effectiveness factor of self-compacting concrete in compression for limit analysis of continuous deep beams. (1st June 2018) - Khatab, Mahmoud A.T.; Ashour, Ashraf
Highlights: Evaluation of different effectiveness factor equations in upper and lower bound analysis of continuous SCC deep beams are presented. A new effectiveness factor expression is suggested to be used for the upper and lower bound solutions. There is a clear disagreement among design codes about selecting the appropriate effectiveness factor. Lower and upper bound analyses are efficient, tools for predicting load capacity of deep beams. For the range of beams considered, proposed effectiveness factor achieved accurate predictions. Abstract: The current design codes, such as ACI 318-14, EC2 and CSA23.3-04, in addition to previous research investigations suggested different expressions for concrete effectiveness factor for use in limit state design of concrete structures. All these equations are based on different design parameters and proposed for normal concrete deep beams. This research evaluates the use of different effectiveness factor equations in the upper and lower bond analyses of continuously-supported self-compacting concrete (SCC) deep beams. Moreover, a new effectiveness factor expression is suggested to be used for upper and lower bound solutions with the aim of improving predictions of the load capacity of continuously-supported SCC deep beams. For the range of deep beams considered, the strut-and-tie method with the proposed effectiveness factor formula achieved accurate predictions, with a mean of 1.01, a standard deviation of 6.7% and a coefficient of variation of 6.8%. For the upper-bound analysis, the predictions of the proposed effectiveness factor equation were more accurate than those of the formulas suggested by previous investigations. Overall, although the proposed effectiveness factor achieved very accurate predictions, further validation for the proposed formula is needed since the only data available on continuous SCC deep beams are those collected from the current study.